2020
DOI: 10.1038/s41467-020-17030-w
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a initiates and perpetuates oncogenic transformation through the regulation of innate immune signaling

Abstract: Genomic instability (GI) predisposes cells to malignant transformation, however the molecular mechanisms that allow for the propagation of cells with a high degree of genomic instability remain unclear. Here we report that miR-181a is able to transform fallopian tube secretory epithelial cells through the inhibition of RB1 and stimulator-of-interferon-genes (STING) to propagate cells with a high degree of GI. MiR-181a targeting of RB1 leads to profound nuclear defects and GI generating aberrant cytoplasmic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
(63 reference statements)
1
27
0
Order By: Relevance
“…Moreover, miR-181a is believed to have the potential as a biomarker for early detection of HGSOC. 134 Indeed, FT194 cells transfected with miR-182 induced tumour growth in 45% (9/20) of the mice, whereas only 10% (1/10) of the mice were detected in the control group. Similar data were repeated in the FT237 cell line.…”
Section: Ta B L E 3 Malignant Transformation Of Immortalized Human Ftecsmentioning
confidence: 95%
“…Moreover, miR-181a is believed to have the potential as a biomarker for early detection of HGSOC. 134 Indeed, FT194 cells transfected with miR-182 induced tumour growth in 45% (9/20) of the mice, whereas only 10% (1/10) of the mice were detected in the control group. Similar data were repeated in the FT237 cell line.…”
Section: Ta B L E 3 Malignant Transformation Of Immortalized Human Ftecsmentioning
confidence: 95%
“…Most recently, miR-181a, that can promote EMT by inhibiting SMAD7 (Fig. 1 ) has been reported to promote oncogenic transformation by increasing genomic instability in fallopian tube epithelial cells, in part through effects on the tumor suppressive s timulator of i nterferon g enes (STING) pathway [ 169 ]. STING and genome instability have in other cancers been reported to be associated with a mesenchymal signature and metastasis, wherein cells with high chromosome instability were enriched for EMT associated genes and pathways [ 170 ].…”
Section: Emt and Metastasis In Epithelial Ovarian Cancermentioning
confidence: 99%
“…Most recently, it has been shown that STING does have tumour‐suppressive activity and the STING pathway is activated in response to cytosolic tumour DNA. Thus, the expression of STING in a subset of HGSCs could reflect some level of ciliated cell differentiation [ 37 ]. In HGSC, a transcriptomic signature characteristic for fallopian tube ciliated cells has been identified and STING was amongst the markers defining ciliated cells, indicating an ability of serous ovarian carcinomas to differentiate into cells that molecularly resemble fallopian tube ciliated cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that a proportion of HGSCs have low STING expression and STING expression could be used as a predictive marker for STING agonist treatment in HGSC. Additionally, miR‐181a targeting of STING has been presented as a therapeutic opportunity [ 37 ]. In cells stably overexpressing mature miR‐181a, knockdown of STING was sufficient to increase cell proliferation and clonogenic survival.…”
Section: Discussionmentioning
confidence: 99%